Between Tradition and Challenges: Identifying Key Factors in Local Community Adaptation to Environmental Change - Rizky Ramadhan; Muhammad Aqshel Revinzky Nizar; Mochamad Chairul Ihsan; Adhadian Akbar; Andreas Recki Prasetyo (CV Putra Publisher, 2025)
Environmental changes resulting from oil palm plantation expansion have become a crucial issue in the discourse on sustainable development in Indonesia, particularly due to their impact on local communities and forest conditions. Although regulations such as the moratorium on oil palm expansion temporarily slowed deforestation, recent trends indicate that land conversion from forest to oil palm plantations is still ongoing. Local communities that have traditionally relied on forest resources are facing complex social, economic, and ecological pressures. This study aims to identify the key factors that shape the adaptive capacity of local communities to environmental changes caused by oil palm expansion. The research location is in the Parindu area, West Kalimantan. The method used is the Analytical Hierarchy Process (AHP), with a pentahelix approach in determining key informants so that decision-making is participatory and multidimensional. The results of this study indicate that institutional resources are the most crucial factor in improving community adaptive capacity. Local institutions—both formal and informal—play a strategic role in bridging local culture with modern economic demands. These findings emphasize the importance of strengthening local institutions to support community adaptation and promote sustainable, equitable, and locally-based development.